The Effect Of Bean Sari On Increasing Breast Milk Production In Breastfeeding Mothers At The Puskesmas Sumbersari : The Effect Of Bean Sari On Increasing Breast Milk Production In Breastfeeding Mothers At The Puskesmas Sumbersari - Erna Amelia Puspita Dewi; Anggraeni, Ernawati (Fetus : Journal of Midwifery, 2025)
Breast milk (ASI) is the result of a physiological process that plays a vital role in supporting infant growth and development, particularly during the early stages of life. Inadequate breast milk production can lead to insufficient nutrient intake for the infant, potentially hindering growth, development, and even cognitive abilities. Although breast milk is naturally produced after childbirth, not all mothers are able to generate it in optimal amounts. Mung bean extract is known to contain various nutrients that contribute to improving breast milk production. Therefore, this study aimed to examine the effect of mung bean extract consumption on breast milk production among breastfeeding mothers in the working area of Puskesmas Sumbersari. Methods: This study used a quantitative approach with a quasi-experimental design and a non-equivalent control group pre-test-post-test method. The study population consisted of 23 postpartum mothers in the Sumbersari Community Health Center area. The study sample consisted of 16 postpartum mothers from day 10 to week two, selected using purposive sampling. Breast milk production data were obtained by measuring changes in infant weight using a digital scale. Data were analyzed using univariate and bivariate methods, with an Independent Samples T-test used for statistical comparisons. Results: The Independent Samples T-test showed a significance value (p-value) of 0.004, which is less than α = 0.05. This indicates that the null hypothesis (H0) is rejected, while the alternative hypothesis (H1) is accepted. Conclusion: There was a significant difference in breast milk production between postpartum mothers who consumed mung bean extract and those who did not, with mung bean extract consumption proven to increase breast milk production. Recommendation: Healthcare workers are encouraged to provide education and motivation to postpartum mothers to consume mung bean extract as a strategy to increase breast milk production